Solid State Ionics 2002
DOI: 10.1142/9789812776259_0061
|View full text |Cite
|
Sign up to set email alerts
|

Water Solubility in Ceria and Zirconia Doped With Rare Earth Oxides

Abstract: In order to understand the solubility of proton in oxides by a new approach using basicity of oxides, the water solubility in ceria and zirconia has been determined by SIMS and FT-IR measurements. From dopant-concentration depending of water solubility, the validity of hydroxyl capacity has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 2 publications
0
55
0
Order By: Relevance
“…While previous work from our laboratory has shown that the impedance of LSM-YSZ cathodes can be constant over a range of current densities, even under anodic polarization, 13 many groups, including ours, have observed significant hysteresis upon cathodic polarization with this material. 13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Therefore, the data from symmetric cells is used qualitatively, primarily to determine whether the material is sensitive to polarization. Based on our previous experience with conventional LSM-YSZ electrodes, 13 an applied current of 250 mA/cm 2 for 10 min is sufficient to give large changes in the ASR measured at OCV.…”
Section: Resultsmentioning
confidence: 99%
“…While previous work from our laboratory has shown that the impedance of LSM-YSZ cathodes can be constant over a range of current densities, even under anodic polarization, 13 many groups, including ours, have observed significant hysteresis upon cathodic polarization with this material. 13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Therefore, the data from symmetric cells is used qualitatively, primarily to determine whether the material is sensitive to polarization. Based on our previous experience with conventional LSM-YSZ electrodes, 13 an applied current of 250 mA/cm 2 for 10 min is sufficient to give large changes in the ASR measured at OCV.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to item ͑i͒, we have reported the change of 18 O diffusion profiles with preannealing temperatures under the nonpolarized condition. 32 The preannealing processes cause the microstructure change and Mn diffusion from LaMnO 3 into YSZ, 14,32 which affects the 18 O diffusion paths at the interface of LaMnO 3 /YSZ ͑although we have adopted the samples at the optimum preannealing temperature͒. With regard to item ͑ii͒, the cell temperature has been carefully controlled in the focused infrared furnace.…”
Section: Resultsmentioning
confidence: 99%
“…19 Secondary ion mass spectrometry analysis ͑SIMS analysis͒ was applied to determine the active sites for 18 O incorporation at the LaMnO 3 mesh/YSZ interface. [20][21][22] Figure 1 shows an example of our SIMS analysis for the mesh-shaped LaMnO 3 on YSZ ͑Fig. 1a͒ and schematic diagram for oxygen transports at the interface ͑Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Oxygen exchange experiments indicate that the reaction zone is close to the TPB or spreads at the interface between LSM and YSZ. 21 Adler et al suggest that the extension of the reaction zone on the free electrode surface is small for LSM. 22 Altogether this indicates that the extension of the reaction zone on LSM or YSZ is relatively small and therefore cannot solely account for the observed activation.…”
Section: Literature Surveymentioning
confidence: 99%